Imagined Common Enemy dan Usaha Konter Radikalisme Komunitas Pemuda Lintas Iman di Yogyakarta - M. Naufal Waliyuddin (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2022)
The radicalism discourse that has been quite widespread in the last two decades has produced various responses, ranging from counter-narrative, deradicalization, and counter-radicalism efforts. This paper investigates, specifically, some motives for countering radicalism organized by the young interfaith peacemaker community (YIPC) in Yogyakarta. Using an interpretive phenomenological approach, this qualitative research explores several motives behind the counter-radicalism movement that they have, at least, three dialectical reasons that trigger them to counter radicalism: collective awareness; imagined common enemy; and the claim of youthfulness. In particular, the factor of this common enemy was born as a result of the hyper-reality that has been created and disseminated by the government, the press, educational institutions which have been concerned with radicalism and terrorism. All these institutional roles systematically and massively stimulate the minds of young people about the dangers that must be fought. Thus their counter-radicalism efforts have sprung up in various forms and approaches.